Circulating human IgG autoanti-IgE antibodies in asthma patients block the binding of IgE to its high affinity receptor. Issue 3 (June 1995) - Smith, S J; Galvin, A; Hall, I; Shakib, F
Abstract : Aims —To investigate the ability of circulating human IgG autoanti-IgE antibodies from asthma patients to block the binding of IgE to the α chain of the high affinity receptor (FcεRI). Methods —This involved the use of a well validated flow cytometric method to detect inhibition of FITC labelled IgE binding to a fibroblast cell line (CHK1E1) transfected with the α chain of FcεRI. Results —IgG autoanti-IgE-containing sera blocked the binding of IgE-FITC to the CHK1E1 cells. No such inhibition was demonstrable with rheumatoid sera containing autoanti-IgG (that is, rheumatoid factor) but lacking autoanti-IgE. Percentage inhibition (up to 50%) of IgE binding to the CHK1E1 cells was directly related to the titre of IgG1, but not IgG4, autoanti-IgE in the sera tested (correlation coefficient 0·66, probability 0·003). Conclusions —The capacity of anti-IgE to block the binding of IgE to FcεRI has important clinical implications, particularly in terms of downregulation of allergic reactions.